ANALISIS PENGARUH DANA PIHAK KETIGA,NON PERFORMING LOAN, DAN SUKU BUNGA PINJAMAN TERHADAP PENYALURAN KREDIT MODAL KERJA, INVESTASI, DAN KONSUMSI BANK PEMBANGUNAN DAERAH (PERIODE 2003-2013) - Binangkit, Yogi Lingga (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aimstodetermine the effect ofthird-party funds(DPK), non-performing loan(NPL), andinterest rates on loans(SB) onworking capital loans, investment, andconsumptioninthe RegionalDevelopment BanksthroughoutIndonesiain the period2003-2013. This research isdescriptiveandquantitativedata usedare secondary dataandquarterly. Method ofmultiple linear regressionanalysis usingOLS. Researchresultsshowedthat simultaneousDPK, NPL, andSBhasa significant effect onthe variableworking capital loans, investment, andconsumption. Inparisalworking capital loanssignificantly affectedbyDPK(+), NPL(+) andinterest rates(-), theinvestmentcredit significantly affectedby DPK(+) andinterest rates(-), and consumer credit significantlyinfluencedbyDPK(+) ,NPL(-), and theinterest rate(+). In general,variabledepositsarethe mostdominant influence oncredit. The ratecoefficient of determination (R2)for thevariablesthat affectworking capital loansamounted to97.1%, which means the freevariablesin the model isable to explainthe variableworking capital loansat 97.1%, the remaining2.9% is explainedbyvariablesoutside the modelthis. as well asthe levelof investmentcreditof R2is 93.7% , the remaining 6.3% explained byvariablesoutside the model, consumer loanhas R2in the amount of97.7%, and the remaining 2.3% explained byvariablesoutsidethe model. Keywords : Credit, Deposit, NPL, Interestrate